The Strategies of the ZISWAF CTARSA Institution in Fundraising and Allocating ZISWAF - Nursyabani, Cahyania; Musaada, Wiwit; Huda, Nurul (UI Scholars Hub, 2024)
Zakat, infaq, alms, and waqf (ZISWAF) are Islamic social finance instruments that contribute to improving community welfare. On this basis, the CT ARSA Foundation established the ZISWAF CTARSA Institution. This study aims to determine the strategies of the ZISWAF CTARSA Institution in managing ZISWAF funds. The research method used is descriptive-qualitative with a field study approach. The data used came from interviews and literature studies. The results showed that the ZISWAF CTARSA Institution, as a relatively new institution, has successfully managed ZISWAF funds. ZISWAF's fundraising activities have proven to be very effective, both online and offline. The distribution model of ZISWAF funds is also right on target and by Sharia principles and emphasizes financial transparency. The community empowerment program is carried out in economy, education, and health with continuous assistance from the institution. Thus, the ZISWAF CTARSA Institution has succeeded in improving community welfare through the ZISWAF funds it manages.